Comparison of the accuracy of three diagnostic criteria and estimating the prevalence of metabolic syndrome: A latent class analysis - Hossein Ebrahimi (Journal of Research in Medical Sciences, 2019)
Background: Metabolic syndrome (MetS) is a growing public health problem with a worldwide distribution, and its prevalence is rapidly increasing worldwide. Hence, this study aimed to compare the prevalence of MetS based on the International Diabetes Federation (IDF), the National Cholesterol Education Program Expert Panel Adult Treatment Panel III (NCEP ATP III), and the American Association of Clinical Endocrinologists (AACE) diagnostic criteria. Materials and Methods: In this cross-sectional study, a total of 4737 people aged 45–69 years were enrolled in the 2nd phase of Shahroud Eye Cohort Study. We evaluated the prevalence of MetS with 95% confidence intervals by age and sex groups and according to MetS components. The accuracy (sensitivity and specificity) of these three methods was compared using latent class analysis. Finally, kappa statistic was used to determine the agreement between the diagnostic methods. Results: The prevalence of MetS varied from a minimum of 47.2% (as defined by the AACE) to a maximum of 60.0% (as defined by the IDF). The sensitivity of the three diagnostic methods of IDF, NCEP ATP III, and AACE was 98.9%, 94.4%, and 91.1%, respectively, and the specificity of these three methods was 94.6%, 97.0%, and 98.4%, respectively. Moreover, the highest agreement was found between the definition of the IDF and the NCEP ATP III. Conclusion: The IDF diagnostic method has a higher sensitivity for the diagnosis of MetS in Iranian middle-aged people. It is recommended to use this method for identifying more people at risk of MetS.